Update in the Early Management and Reperfusion Strategies of Patients with Acute Ischemic Stroke - Aldo A. Mendez; Edgar A. Samaniego; Sunil A. Sheth; Sudeepta Dandapat; David M. Hasan; Kaustubh S. Limaye; Bradley J. Hindman; Colin P. Derdeyn; Santiago Ortega-Gutierrez (Critical Care Research and Practice)
Acute ischemic stroke (AIS) remains a leading cause of death and long-term disability. The paradigms on prehospital care, reperfusion therapies, and postreperfusion management of patients with AIS continue to evolve. After the publication of pivotal clinical trials, endovascular thrombectomy has become part of the standard of care in selected cases of AIS since 2015. New stroke guidelines have been recently published, and the time window for mechanical thrombectomy has now been extended up to 24 hours. This review aims to provide a focused up-to-date review for the early management of adult patients with AIS and introduce the new upcoming areas of ongoing research.